2021
DOI: 10.3390/antibiotics10020216
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices (KAP) Survey among Veterinarians, and Risk Factors Relating to Antimicrobial Use and Treatment Failure in Dairy Herds of India

Abstract: The indiscriminate usage of antimicrobials in the animal health sector contributes immensely to antimicrobial resistance (AMR). The present study aims to assess the antimicrobial usage pattern and risk factors for AMR in animal husbandry sector of India. A cross-sectional survey about Knowledge, Attitude, and Practices (KAP) among veterinarians was carried out using a questionnaire comprising of 52 parameters associated with antibiotic use and the emergence of AMR in dairy herds. Respondents’ KAP scores were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 34 publications
18
31
0
Order By: Relevance
“…Although the use of antimicrobials in animals is Timor-Leste is very low, there is potential for future misuse and overuse with farming intensification. Future studies investigating the knowledge, attitudes and practices of animal health professionals and farmers on antimicrobial use would be useful for identify strategies for promoting prudent use of antimicrobials in animals as identified in other studies [79][80][81]. Even in the absence of such studies, early action can be informed by studies conducted in other developing countries [55,58,82].…”
Section: Future Directionsmentioning
confidence: 99%
“…Although the use of antimicrobials in animals is Timor-Leste is very low, there is potential for future misuse and overuse with farming intensification. Future studies investigating the knowledge, attitudes and practices of animal health professionals and farmers on antimicrobial use would be useful for identify strategies for promoting prudent use of antimicrobials in animals as identified in other studies [79][80][81]. Even in the absence of such studies, early action can be informed by studies conducted in other developing countries [55,58,82].…”
Section: Future Directionsmentioning
confidence: 99%
“…The emergence of antibiotic resistance in humans, animals, and the environment is strongly associated with the unnecessary use and misuse of antibiotics [ 1 ]. Antibiotic resistance is a global problem; however, low-and middle-income countries (LMICs) are considered most affected [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…On these small-scale dairy farms, minimal quality control and infrastructure exists and practices, such as non-therapeutic or irrational use of antibiotics in lactating cows, are uncontrolled and unregulated [ 2 , 11 , 12 ]. Such malpractices do not seem as widespread on larger sized dairy farms which have been identified as using antibiotics in a more responsible way than smaller-scale dairy farms [ 1 ]. Overall, however, regardless of the size of the dairy farm, dairy farmers’ knowledge regarding antibiotics and reasons for antibiotic usage is poorly understood [ 2 , 13 ], and questions related to antibiotic practices, like quantity used, motive, administration method, frequency given, who administers, as well as adherence to withdrawal periods, remain poorly defined in the literature [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increased workload can also play an important role, as veterinarians fear to revisit when the animal did not improve after the first treatment, and they are called again [ 58 ]. Furthermore, veterinarians fear they will be blamed if antibiotics later prove necessary [ 58 , 63 ]. Similar results are reported in a Dutch study in 2015, where veterinarians confirmed that the perceived pressure from clients can be a driver for antibiotic use [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important factors in veterinarians governing the selection of an antibiotic for treatment is their own experience [ 46 , 59 , 63 ]. The lack of experience and confidence might be a reason for a higher amount of antibiotics used for the treatment of NCD carried out by younger colleagues.…”
Section: Discussionmentioning
confidence: 99%